Chronic hypoxia induces the activation of the Wnt/β-catenin signaling pathway and stimulates hippocampal neurogenesis in wild-type and APPswe-PS1ΔE9 transgenic mice in vivo - Varela-Nallar, Lorena; Rojas-Abalos, Macarena; Abbott, Ana C.; Moya, Esteban A.; Iturriaga, Rodrigo; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2014)
Hypoxia modulates proliferation and differentiation of cultured embryonic and adult stem cells, an effect that includes β-catenin a key component of the canonical Wnt signaling pathway. Here we studied in vivo the effect of mild hypoxia on the activity of the Wnt/β-catenin signaling pathway in the hippocampus of adult mice. As a molecular control of the physiological hypoxic response the hypoxia-inducible transcription factor-1α (HIF-1α) was analyzed. Exposure to chronic hypoxia (10% oxygen for 6-72 h) stimulated the activation of the Wnt/β-catenin signaling pathway. Because the Wnt/β-catenin pathway is a positive modulator of adult neurogenesis, we evaluated whether chronic hypoxia was able to stimulate neurogenesis in the subgranular zone (SGZ) of the hippocampal dentate gyrus. Results indicate that hypoxia increased cell proliferation and neurogenesis in adult wild-type mice as determined by Ki67 staining, BrdU incorporation and double labeling with doublecortin. Chronic hypoxia also induced neurogenesis in double transgenic APPswe-PS1deltaE9 mouse model of Alzheimer’s disease (AD), which shows decreased levels of neurogenesis at the SGZ. Our results show for the first time that in vivo exposure to hypoxia can induce the activation of the Wnt/β-catenin signaling cascade in the hippocampus, suggesting that mild hypoxia may have a therapeutic value in neurodegenerative disorder associated with altered Wnt signaling in the brain and also in pathological conditions in which hippocampal neurogenesis is impaired.